2014
DOI: 10.1007/s10616-014-9764-6
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic contents and antioxidant activity of ethanolic extract of Capparis spinosa

Abstract: Caper plant (Capparis spinosa) extracts have been associated with diverse biological activities including anti-oxidant properties. In this work, we characterized the hydro-ethanolic extract obtained from C. spinosa leaves [hydroethanolic extract of C. spinosa (HECS)] by analyzing the content in antioxidant compounds such as polyphenols, flavonoids and anthocyanins. Further, we evaluated HECS antioxidant activities in vitro using bleaching of 1,1-diphenyl-2-picrylhydrazyl radical and ABTS test as well as by pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 23 publications
0
41
1
1
Order By: Relevance
“…In fact, it is known that glucosinolates possess anti‐cancerogenic properties . Moreover, Capparis species contain polyphenols and flavonoids, which are known to possess many beneficial biological activities …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, it is known that glucosinolates possess anti‐cancerogenic properties . Moreover, Capparis species contain polyphenols and flavonoids, which are known to possess many beneficial biological activities …”
Section: Introductionmentioning
confidence: 99%
“…[2,17] In fact, it is known that glucosinolates possess anticancerogenic properties. [11,18] Moreover, Capparis species contain polyphenols and flavonoids, [19,20] which are known to possess many beneficial biological activities. [21] High-performance liquid chromatography coupled to mass detection (HPLC-MS) is the most frequently used technique for the separation and the selective detection of both glucosinolates and phenols.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, the plant tissue culture conditions involved in levels of plant secondary metabolites such as phenols, flavonoids, polyphenols, tocopherols, and derivatives of cinnamic acid [13,14]. Phenolic compounds and flavonoid compounds are very important plant constituents because of their radical scavenging ability resulting from their hydroxyl groups [15][16][17][18]. The results showed different outcome with the shoot clumps extract of tissue-cultured R. australis and the natural R. australis extract.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study has revealed that an N-butanol extract of caper induced apoptosis through mitochondrial pathway [22]. In addition, hydro-ethanolic extract obtained from C. spinosa leaves has been demonstrated to exhibit antioxidant activity in both chemical and biological tests [23]. In Male Chinese Kun Ming mice, an acute inflammation in mice hind paws by subcutaneously injection of Carrageenan has been induced, and the anti-inflammatory effects of C. spinosa aqueous extract was evaluated with calculating of the paw edema "or inhibition rate" [23].…”
Section: Antioxidant Anti-allergic and Anti-inflammatory Activitiesmentioning
confidence: 99%
“…In addition, hydro-ethanolic extract obtained from C. spinosa leaves has been demonstrated to exhibit antioxidant activity in both chemical and biological tests [23]. In Male Chinese Kun Ming mice, an acute inflammation in mice hind paws by subcutaneously injection of Carrageenan has been induced, and the anti-inflammatory effects of C. spinosa aqueous extract was evaluated with calculating of the paw edema "or inhibition rate" [23]. After oral administration C. spinosa extract induced a significant anti-inflammatory activity against carrageenan-induced edema.…”
Section: Antioxidant Anti-allergic and Anti-inflammatory Activitiesmentioning
confidence: 99%